Development of anti-Crimean-Congo hemorrhagic fever virus Gc and NP-specific ELISA for detection of antibodies in domestic animal sera - Belij-Rammerstorfer, Sandra; Limon, Georgina; Maze, Emmanuel A.; Hannant, Kayleigh; Hughes, Ellen; Tchakarova, Simona R.; Alexandrov, Tsviatko; Mmbaga, Blandina T.; Willett, Brian; Booth, George; Lyons, Nicholas A.; Baker, Natalie; et al. (Frontiers in Veterinary Science, 2022)
Crimean-Congo haemorrhagic fever (CCHF) is a priority emerging disease. CCHF, caused by CCHF virus (CCHFV), can lead to haemorrhagic fever in humans with severe cases often having fatal outcomes. CCHFV is maintained within a tick-vertebrate-tick cycle, which include domestic animals. Domestic animals infected with CCHFV do not show clinical signs of the disease and the presence of antibodies in the serum can provide evidence of their exposure to the virus. Current serological tests are specific to either one CCHFV antigen or the whole virus antigen. Here, we present the development of two in-house ELISAs for the detection of serum IgG that is specific for two different CCHFV antigens: glycoprotein Gc (CCHFV Gc) or nucleoprotein (CCHFV NP). We demonstrate that these two assays were able to detect anti-CCHFV Gc-specific and anti-CCHFV NP-specific IgG in sheep from endemic CCHFV areas with high specificity, providing the new insight into heterogeneity of the immune response induced by natural infection with CCHFV in domestic animals.